A systematic review of design solution for urban agriculture in allotment areas - Maryam Jahed; Seyed-Abbas Yazdanfar; Saeid Norouzian-Maleki (علوم محیطی)
Introduction:Alteration of greenland into residential areas is one of the effects of growing cities; this has caused many environmental and dietary problems. As greenland converted to urban areas, fields shrunk, so food security decreased. Lack of management about wastes results in increasing air and water pollution. Tehran has encountered this problem like other metropolitan cities. Urban agriculture can solve all those problems, because urban agriculture projects can affect different aspects of the city. Previous research showed improvement in biodiversity, increasing employment, increasing food security, better waste management, communication growth, decreasing air pollution, etc., are results of implementing urban agriculture in cities. However, there are many barriers that disturb urban agriculture. Based on the review, barriers like the problem of landowners, privacy issues, and lack of knowledge about buildings, crop requirements, and suitable conditions for security were discovered in articles. Many of these barriers are visible in metropolitans like Tehran. Some researchers sought for solving problems, but still, no studies worked about building details in urban agriculture. Therefore, this study aims to review studies on urban agriculture to achieve codes about implementing urban agriculture in metropolitan cities.Material and methods: This article aimed to achieve its goal by reviewing articles with standard systematic procedure. Records were extracted from Web of Science, IEEE, JSTOR, Science Direct, and Magiran. In the first step, 1259 records were identified by searching “urban agriculture” as the main keyword. By applying “design urban agriculture” and “planning urban agriculture” as keywords, 1119 records were excluded, and 140 articles remained. All 140 abstracts of articles were reviewed. One-hundred-ten records articles were excluded because they did not meet our article criteria, remaining only 30 articles. For assessing the strength of the body of evidence, the CASP checklist was used. At the end, only articles that took 7 or more from the CASP checklist were remained. Finally, 18 articles were analyzed for the conclusion.Results and discussion:Among 18 articles, 10 articles were related to (Pri-Urban Agriculture) PUA, 7 records were related to UA and combining requirements of agriculture with buildings and 1 article was related to natural recourse related to urban agriculture. All data were categorized in four fields: legal, technical, agricultural, and security. First of all, the legal field was about legislation related to urban agriculture and different aspects of the partnership. The technical category assessed related rules to building, urban lands, and their effects on the body of the city. The agricultural framework was concerned with plant’s needs such as light, wind speed, nutrition, and requirements of the soil. Security category contained codes about improving the security of pathway to urban agriculture zone, roof security requirements, and control on allotment area to prevent from vandalism, etc.Conclusion:Results of this study showed that urban agriculture is achievable in Tehran. Furthermore, it is functional for solving problems. Proposing urban agriculture in designing green zones and landscapes can have different results on the city, like improving food security, increasing communicational contacts, better use of natural resources, and empowering biodiversity. Therefore, it is recommended that designers put urban agriculture as a priority.